Zechariah 5:5-11: Why an ephah? - Seufert, Matthew (2015)
Scholars have offered many suggestions for understanding the ephah in Zechariah 5:5-11 without consensus. An allusion to Jeremiah 3:2 offers a new possibility. The הָאֵיפָה (ephah) in Zechariah recalls and localizes the אֵיפֹה (where) of Israel’s harlotry recounted in Jeremiah.
Keywords: Zechariah 5:5-11 -- ephah -- woman -- allusion -- Jeremiah 3